Climate change in international law - Ramírez Bañuelos, Jesús Francisco (2021)
Using a critical approach, this essay documents the principles of international law that have an impact on climate change. It then identifies the resources available to States and individuals to demand compliance with climate change obligations and assesses their chances of success. Finally, a new approach is put forward that would help solve conflicts more effectively.